(untitled) (Acta Scientiarum. Animal Sciences, 2018)
This study evaluated the effect of increasing levels of leucaena forage in sorghum: forage. In addition to pure sorghum, it was evaluated different levels of inclusion of leucaena (15, 30 and 50%) at the time of ensiling. Forage was ensiled in PVC tubes (100 mm diameter, 500 mm length) under the density of 500 – 600 kg m-3, a total of 20 silos were prepared, which were opened 35 days after ensiling. There was no effect (p > 0.05) of leucaena inclusion levels for pH, water activity (Aw) and total ammonia nitrogen (total NH3-N). There was an increasing linear effect (p < 0.05) for the content of dry matter (DM), crude protein (CP) and lignin that increased from 33.47 to 34.75%, 7.82 to 16.05% and from 7.29 to 9.93%, at the levels from 0 to 50% inclusion of leucaena, respectively. There was a decreasing linear effect (p < 0.05) for neutral detergent fiber corrected for ash and protein (NDFcp) and hemicellulose, which reduced from 56.65 to 48.37% and from 24.07 to 17.67% at the levels of 0 and 50% inclusion, respectively. For the ash content, there was a quadratic effect (p < 0.05), with a maximum at 8.3% with 8.9% inclusion of leucaena. The inclusion of up to 50% leucaena into sorghum silage is recommended, because, in addition to maintaining the fermentation quality, it also improved nutritional quality of sorghum silage.